2015
DOI: 10.1371/journal.pone.0141097
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Brain Changes after Climbing to Extreme Altitudes—A Prospective Cohort Study

Abstract: BackgroundFindings of cerebral cortical atrophy, white matter lesions and microhemorrhages have been reported in high-altitude climbers. The aim of this study was to evaluate structural cerebral changes in a large cohort of climbers after an ascent to extreme altitudes and to correlate these findings with the severity of hypoxia and neurological signs during the climb.MethodsMagnetic resonance imaging (MRI) studies were performed in 38 mountaineers before and after participating in a high altitude (7126m) clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…From surface-based morphology analysis, we revealed that there were no significant differences of cortical volume between the Year 2 and the baseline in both experimental and control group. This agrees with previous findings by Kottke et al (2015), which evaluated the occurrence of structural cerebral changes in a cohort of 38 recreational HA climbers and did not detect structural changes (Kottke et al, 2015). However, some fMRI studies found that compared with the SL individuals, HA young adults who were born and grew up at plateau had decreased volume in the left insula, left inferior parietal gyrus, and right superior parietal gyrus and increased in the left precentral cortex and multiple sites in cerebellar cortex (Usui et al, 2004;.…”
Section: Discussionsupporting
confidence: 92%
“…From surface-based morphology analysis, we revealed that there were no significant differences of cortical volume between the Year 2 and the baseline in both experimental and control group. This agrees with previous findings by Kottke et al (2015), which evaluated the occurrence of structural cerebral changes in a cohort of 38 recreational HA climbers and did not detect structural changes (Kottke et al, 2015). However, some fMRI studies found that compared with the SL individuals, HA young adults who were born and grew up at plateau had decreased volume in the left insula, left inferior parietal gyrus, and right superior parietal gyrus and increased in the left precentral cortex and multiple sites in cerebellar cortex (Usui et al, 2004;.…”
Section: Discussionsupporting
confidence: 92%
“…Details on subject selection criteria are provided elsewhere (Kottke et al . ). All subjects underwent examination of the sublingual microcirculation by handheld vital microscopy (HVM) before and after topical application of nitroglycerin, alongside a clinical examination, echocardiography, and venous and arterial blood sampling for baseline assessment at the University Hospital of Bern (sea level, SL; 553 m).…”
Section: Methodsmentioning
confidence: 97%
“…Studies of oxygenation in healthy participants on high altitude expeditions have shown that it is possible to tolerate hypoxemia quite well [37]. However, there seems to be a risk for cerebral lesions and microhemorrhages in association with high altitude, i.e., hypobaric hypoxemia [38]. Nevertheless, these conditions are difficult to compare with those seen in patients with an underlying disease suffering from hypoxemic respiratory failure.…”
Section: Hypoxemia and Hypoxiamentioning
confidence: 99%
“…Five patients were previous healthy. Five patients presented with co-morbidities and had a median body mass index (BMI, kg/m 2 ) of 35 (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). A person with a BMI of 30 or more is generally considered obese according to the world health organization's (WHO) definition [44].…”
mentioning
confidence: 99%